Characterization of sago starch-based degradable plastic with agricultural waste cellulose fiber as filler - Dewi, Rozanna; Sylvia, Novi; Zulnazri, ,; Riza, Medyan; Siregar, Januar Parlaungan; Cionita, Tezara; Kusuma, Budhi Santri (American Institute of Mathematical Sciences, 2024)
Sago starch and cellulose fiber can be used as a raw material for making degradable plastics to replace commercial plastics. This research used corn cob fiber and sugarcane bagasse fiber as filler to improve the properties of degradable plastic. The research method consists of several stages, cellulose fiber preparation, degradable plastic synthesis and plastic characterization. The result showed tensile strength of plastic with corn cob and sugarcane bagasse filler was 6.37–11.5 MPa and 9.70– 16.47 MPa, respectively. The compound composition test through Fourier Transformation Infra-Red (FTIR) exhibited hydrophilic behavior, hence plastic easily degraded by soil. Differential Scanning Calorimetry (DSC) shows that degradable plastic with corn cob fiber filler denoted a melting point of 163.84 °C, while sugarcane bagasse fiber filler at 163.47 °C. Thermogravimetric Analysis (TGA) analysis indicated degradable plastic had a good thermal stability. Scanning Electron Microscopy (SEM) exhibited few white lumps and indentations on the surface, indicating that the solubility was not homogeny and could be due to the influence of stirring process. In term of ability to absorb water, both plastic with fiber filler had a small water absorption with a range of 5–6%. Melt Flow Rate (MFR) analysis of degradable plastics with corn cob fiber and sugarcane bagasse pointed the value that was suitable for injection molding processing technique. The degradation of both plastics ranged about 50– 85 days to completely decomposed naturally in soil, as supported by FTIR analysis.